Hepatitis B Virus Screening Before Cancer Chemotherapy in Taiwan: A Nationwide Population-Based Study - Sun, Wei-Chih; Tang, Pei-Ling; Chen, Wen-Chi; Tsay, Feng-Woei; Wang, Huay-Min; Tsai, Tzung-Jiun; Kao, Sung-Shuo; Cheng, Jin-Shiung; Tsai, Wei-Lun (Frontiers in Medicine, 2021)
Background: Reactivation of the hepatitis B virus (HBV) during cancer chemotherapy is a severe and sometimes fatal complication. In 2009, the National Health Insurance (NHI) in Taiwan recommended and reimbursed screening for HBV infection and prophylactic antiviral therapy before cancer chemotherapy. In this study, we determined the HBV screening rate in patients with cancer undergoing chemotherapy in Taiwan. Methods: We retrospectively collected data from the National Health Insurance Research Database on patients who received systemic chemotherapy for solid or hematologic cancers from January 2000 through December 2012. We defined HBV screening based on testing for serum HBsAg within two years of the first chemotherapy commencement. We calculated overall and annual HBV screening rates in all patients and subgroups of age, gender, cancer type, hospital level, physician’s department, and implementation of NHI reimbursement for HBV screening before cancer chemotherapy. Results: We enrolled 379,639 patients. The overall HBV screening rate was 45.9%. The screening rates were higher in males, those with hematological cancer, those at nonmedical centers and medical departments. The HBV screening rates before (2000–2008) and after the implementation of NHI reimbursement (2009–2012) were 38.1% and 57.5%, respectively (p < 0.0001). The most common practice pattern of HBV screening was only HBsAg (64.6%) followed by HBsAg/HBsAb (22.1%), and HBsAg/HBcAb/HBsAb (0.7%) (p < 0.0001). The annual HBV screening rate increased from 31.5% to 66.3% (p < 0.0001). The screening rates of solid and hematological cancers significantly increased by year; however, the trend was greater in solid cancer than in hematological cancer (35.9% & 26.2%, p < 0.0001). Conclusions: The HBV screening rate before cancer chemotherapy was fair but increased over time. These figures improved after implementing a government-based strategy; however, a mandatory hospital-based strategy might improve awareness of HBV screening and starting prophylactic antiviral therapy before cancer chemotherapy.